Adsorption performance of biochars from agricultural and forestry wastes. Issue 4 (February 2021) - Ren, Xiaoli; Tan, Ying; Lai, Xuehui; Zhu, Kaijin
Abstract: Four types of biochars were prepared by using sawdust, corn straw, peanut hull and fallen leaves as materials, respectively. The characteristics of four types of biochars were analyzed by SEM, FTIR and BET, the SBET of SDC, PHC, CSC and FLC were 1168.45, 846.95, 825.51 and 401.26m 2 ·g −1 . The adsorption conformed to the pseudo-second-order model and the Langmuir isotherm.